A new peculiar species of Anaclileia Meunier (Diptera: Mycetophilidae) from Georgia, Transcaucasia - Kurina, Olavi (Entomologica Fennica, 2018)
A new fungus gnat species, Anaclileia adjarica sp. n. (Diptera:Mycetophilidae) from Georgia is described, illustrated and discussed. The species represents the first record of the genus from Georgia as well as from whole Caucasus region. The new species is distinguished by the peculiar and unique structure of the male terminalia, especially that of the tergite 9 which includes posterolateral megasetae and a heart-shaped aggregation of small spines. The possible distributional range of the new species is discussed.